The Influence of Tiktok Live Streaming and Influencer Engagement on Consumers Purchase Intention: A Systematic Literature Review - Damania, Alfina; Quro, Umul; Nurlisyana, Wina; Aulia, Windy (Postgraduate, University of Mataram, 2026)
Digital developments have brought significant changes in product marketing and marketing. TikTok, one of the entertainment platforms, has now become an effective marketing channel. This study aims to analyze the influence of TikTok live shopping and influencers on purchase intention through a systematic and comprehensive approach. This research method is a synthetic literature review (Systematic Literature Review/SLR) supported by the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) framework, analyzing 10 selected journas from 2021 to 2025 obtained from various reputable academic databases such as Scopus, Web of Science, ScienceDirect, and Google Scholar. The results of the study indicate that TikTok live streaming or live shopping influences consumer purchase intention because interactivity and the quality of the real-time experience have important roles as determinants of purchase intention. In addition, influencers influence TikTok consumer purchase intention by being influenced by several factors, such as credibility, authenticity, and emotional connection. It is recommended that further research develop a more holistic conceptual model of how digital social influence and interactive experiences shape modern consumption behavior, while also providing a solid theoretical foundation for subsequent SLR research and scholarly publications.